Response to comment on 'Valid molecular dynamics simulations of human hemoglobin require a surprisingly large box size' - Krystel El Hage; Florent Hédin; Prashant K Gupta; Markus Meuwly; Martin Karplus (eLife, 2019)
We recently reported that molecular dynamics simulations for hemoglobin require a surprisingly large box size to stabilize the T(0) state relative to R(0), as observed in experiments (El Hage et al., 2018). Gapsys and de Groot have commented on this work but do not provide convincing evidence that the conclusions of El Hage et al., 2018 are incorrect. Here we respond to these concerns, argue that our original conclusions remain valid, and raise our own concerns about some of the results reported in the comment by Gapsys and de Groot that require clarification.